Radioactive Dose Measurement Based on SPECT Gamma Camera: Patient’s Dose - Zobly, Sulieman M. S.; O.Osman, Abdelbagi (Gezira Journal of Health Sciences, 2015)
A dose measurement is one of the main steps in nuclear medicine imaging, which is done before radiotracer injection of patient. There are different types of instruments used for dose measuring; the most common instrument used is a dose calibrator. So as to get accurate value of the measured dose, the dose calibrator has to be well calibrated regularly. In most cases we need to send the dose calibrator to the manufacturer, standardized organization or reference laboratory for recalibration. Recalibrating the dose calibrator in our department or even in Africa is a challenge. Thus we need to send the instrument to the manufacturer, which costs a lot and takes long time. In this work we want to make use of SPECT gamma camera for measuring the patient dose instead of using a dose calibrator to avoid stopping the work during sending the dose calibrator for calibration or when this device is broken down. We compared the doses that were measured in both the gamma camera and in the dose calibrator device. We developed an equation to enable us to measure the amount of patient dose using SPECT gamma camera. The proposed algorithm validated using different patient doses. The proposed dose measurement algorithm gives the same reading that was obtained with dose calibrator.